2014
DOI: 10.1159/000368264
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid-Induced Sodium Appetite and Renal Salt Retention: Evidence for Common Signaling and Effector Mechanisms

Abstract: An increase in renal sodium chloride (salt) retention and an increase in sodium appetite are the body's responses to salt restriction or depletion in order to restore salt balance. Renal salt retention and increased sodium appetite can also be maladaptive and sustain the pathophysiology in conditions like salt-sensitive hypertension and chronic heart failure. Here we review the central role of the mineralocorticoid aldosterone in both the increase in renal salt reabsorption and sodium appetite. We discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 107 publications
(127 reference statements)
3
26
0
Order By: Relevance
“…Known target genes of theoretical interest, including the aldosterone-inducible subunits of the renal epithelial Na + channel, ENaC ( Scnn1a, Scnn1b and Scnn1g ), which also serves as the taste receptor for salt, were absent in control and deprived NTS HSD2 neurons (Figure S4A). Furthermore, consistent with the lack of a role for this otherwise attractive candidate (Fu and Vallon, 2014), the ENaC blocker amiloride did not inhibit firing of NTS HSD2 neurons from Na + -deprived mice (Figure S4C). On the other hand, NTS HSD2 neurons did express the aldosterone/MR target gene, serum/glucocorticoid regulated kinase 1 ( Sgk1 ), which in the kidney mediates aldosterone-induced trafficking of ion channels.…”
Section: Resultssupporting
confidence: 61%
“…Known target genes of theoretical interest, including the aldosterone-inducible subunits of the renal epithelial Na + channel, ENaC ( Scnn1a, Scnn1b and Scnn1g ), which also serves as the taste receptor for salt, were absent in control and deprived NTS HSD2 neurons (Figure S4A). Furthermore, consistent with the lack of a role for this otherwise attractive candidate (Fu and Vallon, 2014), the ENaC blocker amiloride did not inhibit firing of NTS HSD2 neurons from Na + -deprived mice (Figure S4C). On the other hand, NTS HSD2 neurons did express the aldosterone/MR target gene, serum/glucocorticoid regulated kinase 1 ( Sgk1 ), which in the kidney mediates aldosterone-induced trafficking of ion channels.…”
Section: Resultssupporting
confidence: 61%
“…[28][29][30][31][32][33] As aforementioned, the GI tract is the first organ exposed to ingested sodium. In the saltdepleted state, sensing the need for sodium in the tongue and stomach would lead the person to ingest more salt, 34 and in the addition, make the GI tract secrete hormones that increase absorption/reabsorption of sodium in different organs in the body, including the kidney. The converse occurs in the salt-replete state; less salt is ingested and the GI tract triggers the mechanisms to induce natriuresis and diuresis.…”
Section: Renal Regulation Of Sodium Homeostasismentioning
confidence: 99%
“…Fu et al [199] have assumed that aldosterone activates SGK1, Nedd4-2 and ENaC in both kidney and brain. They suggested that SGK1 and ENaC were involved in aldosterone-induced salt appetite, as ENaC also mediates the gustatory salt sensing.…”
Section: Physiological Role Of Sgk1 In Na+ Transportmentioning
confidence: 99%